Dynamic thermal response of bast fiber assemblies - Qu Li-Jun (Thermal Science, 2014)
Dynamic thermal response of several common bast fiber assemblies was investigated, the dynamic temperature curves of fiber assemblies under high temperature (100°C) were measured and a dynamic heat transfer coefficient was proposed to elucidate the dynamic heat transfer performance during the initial unsteady heat transfer process. The result showed that the dynamic heat transfer performance of bast fibers was better than that of cotton fibers.